Burn Out Among Medical Interns: A Cross Sectional Study - Dr Siva Keerthika S,; Dr Santosh Biradar,; Dr Vinod S Kamble,; Dr Shrinivas Reddy, (International Journal of Pharma and Bio Sciences, 2024)
Burnout or chronic stress exhaustion is connected to high-stress occupations, a widespread problem among health care workers. Medical Interns are a vulnerable group to experience burnout, as they are exposed to stressors like long working hours, night shifts, lack of free time, lack of sleep, and recreational activities. It is also a transition period from being a medical student to a working doctor, which comes with responsibilities. These factors make them susceptible to mental aggravations, such as burnout syndrome, that are not always evaluated. In this regard, a study was done among medical interns to assess the prevalence of burnout and identify the associated factors. This cross-sectional study was conducted among 96 medical interns at ESIC Medical College in Kalaburagi over three months from November 2022 to January 2023. Burnout was evaluated by using the Maslach Burn Out Inventory. Based on the scores, individuals were classified as high-level, moderate-level, and low-level burnout. Burnout was observed in 22.91% of participants. 25% of participants scored high on the emotional exhaustion subscale, 55.20% scored high on the depersonalization subscale, and 60.42% scored low on the personal accomplishment subscale. A statistically significant association was found between resting interval, the total number of monthly night shifts, and burnout. The study showed that medical interns experience burnout, which has to be handled individually and by creating a conducive working environment.